What do Street Children Need in the Shelter Home: A Narrative Review Study? - Fitriani, Lisa; Saidi, Sanisah; Susanti, Suryani Sulistiana (CV. Global Health Science Group, 2024)
Issues with street children, particularly in developing countries, seem to be alarming. Many countries reported increasing numbers. The aim of this research is to explore the experience support of street children in the shelter home, the question on how the experience of these street children when they are being placed in the shelter homes, and what the type of support is given to them? A comprehensive search of relevant databases from 2010 to August 2021 with critical key search focuses on the “street children's welfare